LOCAL TRADITIONS AND THE DYNAMICS OF DIVERSITY IN NEGERI WARAKA - Ambarita, Jenri; Siahaya, Agusthina; Park Mi Kyong (Balai Penelitian dan Pengembangan Agama Jakarta, 2024)
This research explores religious diversity and the value of harmony in the traditions of the Waraka community using a descriptive qualitative approach. The primary objective is to analyze how religious diversity is recognized in daily life and how values of harmony are promoted through their traditions. Data collection methods include in-depth interviews, direct observation, and document review with key informants such as the King of Waraka, his wife, religious leaders from Christianity, Catholicism, and Islam, as well as community members from various religions, including the King’s daughter-in-law from Manado. The collected data was analyzed using Miles and Huberman’s data analysis techniques. The findings show that the Waraka community practices interfaith tolerance through the joint construction of places of worship and shared religious celebrations. Traditions like “Ronda Kambing” and “Natsar Negeri” serve as concrete examples of interfaith interaction that strengthen social understanding. This research concludes that the religious harmony practices in Waraka can inspire the creation of inclusive and tolerant societies globally, with an emphasis on educational approaches and more structured interfaith dialogue.